Social housing opportunities and challenges: Perspectives from Denmark, Germany, Portugal and Serbia - Sónia Alves; Hans Thor Andersen; Els Keunen; Zlata Vuksanović-Macura (Verlag der ARL - Akademie für Raumentwicklung in der Leibniz-Gemeinschaft, 2026)
In recent decades, European housing systems have faced significant challenges, including rising socioeconomic inequalities, demographic shifts, welfare cuts, the financialization of housing markets, and ongoing affordability crises. The Delivering Safe and Social Housing (DASH) project, carried out by a consortium of institutions from Denmark, Germany, Portugal, and Serbia, explores these issues by comparing national social and affordable housing regimes and approaches and practices in medium-sized cities (Aalborg, Tübingen, Braga, and éCaécak). This publication aims to highlight both the structural differences and similarities in providing social and affordable housing opportunities. The findings reveal the notable diversity of European housing systems. Denmark's universalist, association-based model contrasts with Serbia's residual, ad hoc approach; Germany blends limited social housing with broader rent controls, while Portugal has traditionally focused on homeownership, but it now recognises the need for a regulated, publicly owned rental sector serving low- and middle-income families. These paths, influenced by factors such as postsocialist privatisation, economic crises, or welfare reforms, show how social housing remains highly dependent on context. Nonetheless, common issues remain: matching housing supply with changing demographics and mobility; financing provision under fiscal constraints and increasing construction costs; and tackling urban pressures from gentrification, tourism, and migration. Policy debates include Denmark's contested "parallel societies" laws, Portugal's EU-funded reforms, Germany's efforts to increase supply amid inflation risks, and Serbia's limited political focus on housing. At the local level, innovative municipal strategies present promising options. At a time when European focus on affordability is renewed, this publication demonstrates how diverse histories, institutional frameworks, and local initiatives come together around the urgent need to secure social housing as a key element of fair and sustainable urban growth.
Keywords: 710; Social housing; affordability; housing policy; international comparative analysis; Europe